Benefits of simulations as remote exercises during the COVID-19 pandemic: an enzyme kinetics case study - Worrall, AF; Bergstrom Mann, PE; Young, D; Wormald, MR; Cahill, ST; Stewart, MI (American Chemical Society, 2020)
Teaching practical chemistry skills remotely is not a task that would have been high on the agenda only a few months ago. However, in light of the COVID-19 pandemic, students around the world are having to work from home, and the chemistry education community has been forced to adapt to the new circumstances. In response, we discuss the use of simulations in place of practical laboratory work, with emphasis on the development of students’ experimental design skills. The simulation of Michaelis–Menten enzyme kinetics is given as an example exercise, which other instructors could implement with immediate effect.